Tracheospasmolytic and anti-inflammatory activity of indigenous Curcuma species as traditional antiasthmatic medicines - SWANDARI PARAMITA; EMIL BACHTIAR MOERAD; SJARIF ISMAIL; EVA MARLIANA (Nusantara Bioscience, 2018)
Paramita S, Moerad EB, Ismail S, Marliana E. 2018. Tracheospasmolytic and anti-inflammatory activity of indigenous Curcuma species as traditional antiasthmatic medicines. Nusantara Bioscience 10: 105-110. Asthma is still a major health problem in the world. Antiasthma drugs raise the problem of side effects and medical expenses. Thus, it is necessary to develop medicinal plants based antiasthma drugs with fewer side effects and more affordable costs. The potential antiasthma medicinal plant came from the genus of Curcuma (Zingiberaceae family). Turmeric (Curcuma longa L.) is the most prominent species in this genus and has been extensively studied for the treatment of asthma. However, there are other Curcuma indigenous species that are also traditionally used for asthma, namely Curcuma aeruginosa Roxb. and Curcuma mangga Val. Zijp. Both indigenous species have not been studied pharmacological activity as an antiasthma. This research was conducted to know the tracheospasmolytic activity of ethanol extract of C. aeruginosa and C. mangga on the separate organ of guinea pig trachea to determine the antiasthma effect. The research was also conducted to know anti-inflammatory activity with membrane stabilization test and inhibition of lipoxygenase. Results showed that C. aeruginosa and C. mangga had lower tracheospasmolytic activity when they were compared with aminophylline as a positive control. However, the EC50 value of C. aeruginosa (0.020 ± 0.004) and C. mangga (0.039 ± 0.005) were not significantly different with aminophylline (0.016 ± 0.005) as positive controls. The result of membrane stabilization test showed that the EC50 value of C. aeruginosa (47.76 ± 1.57) and C. mangga (67.50 ± 0.97) were high when they were compared with indomethacin (26.39 ± 2.91) as the positive control. Results of lipoxygenase inhibition test showed that the EC50 value of C. aeruginosa (-111.11 ± 2.30) and C. mangga (-101.98 ± 1.32) were high than that of indomethacin (-282.84 ± 7.41) as the positive control. These results show the potential use of C. aeruginosa and C. mangga as antiasthma via tracheospasmolytic activity in separate organs of guinea pig. They also had anti-inflammatory effect based on membrane stabilization and inhibition of lipoxygenase test.